Late radiation-related lymphopenia after prostate stereotactic body radiation therapy plus or minus supplemental pelvic irradiation - Gaudian, Kelly; Koh, Min Jung; Koh, Min Ji; Jermain, Peter; Khan, Irfan; Kallam, Diya; Lee, Zach; Collins, Ryan R.; Zwart, Zoya; Danner, Malika; Zwart, Alan; Kumar, Deepak; et al. (Frontiers in Oncology, 2024)
IntroductionPrior studies suggest lymphopenia following radiation therapy may impact toxicity and cancer control. Chronic radiation-related lymphopenia (RRL) has been noted in prostate cancer patients treated with conventionally fractionated pelvic radiation therapy. The impact of utilizing hypofractionated high integral dose therapies such as stereotactic body radiation therapy (SBRT) on RRL is less well characterized. This prospective study sought to evaluate the impact of prostate SBRT plus or minus supplemental pelvic nodal radiation (PNI) on RRL.MethodsBetween 2012 and 2023, serial serum absolute lymphocyte counts (ALCs) were measured in 226 men treated at MedStar Georgetown with robotic SBRT using the CyberKnife® (CK) (36.25 Gy in 5 fractions) alone or CK (19.5 Gy in 3 fractions) followed by supplemental PNI using VMAT (37.5–45.0 Gy in 15–25 fractions) per an institutional protocol (IRB#: 2012-1175). Baseline ALC (k/μL) was measured 1–2 hours prior to robotic SBRT and at each follow-up appointment (1, 3, 6, 9, 12, 18, and 24 months post-treatment). Lymphopenia was graded using the CTCAEv.4: Grade 1 (0.8-1.0 k/μL), Grade 2 (0.5-0.8 k/μL), Grade 3 (0.2-0.5 k/μL) and Grade 4 (<0.2 k/μL). To compare two different treatment groups, the Wilcoxon signed-rank test was used. A p-value of < 0.05 determined statistical significance.ResultsOf 226 patients (SBRT alone: n = 169, SBRT + PNI: n = 57), the median age was 72 years and 45% of patients were non-white. Baseline lymphopenia was uncommon and of low grade. In the SBRT alone group, the baseline ALC of 1.7 k/μl decreased by 21% to 1.4 k/μL at 3 months and then stabilized. 38% of these men experienced lymphopenia in the two years following SBRT, however, no patient presented with Grade 3 lymphopenia. Patients who received SBRT + PNI had a lower baseline ALC (1.5 k/μl), and a significantly greater decrease in ALC relative to individual baseline value throughout the 2-year follow-up period, decreasing by 57% to 0.6 k/μL at 3 months and recovering to a 36% decrease from baseline (1.0 k/μL) at 24 months. Notably, 12% of the men treated with SBRT + PNI experienced Grade 3 lymphopenia. No patient in either cohort experienced Grade 4 lymphopenia.DiscussionThe low incidence of high-grade lymphopenia within this elderly patient population further supports the safety of prostate SBRT plus or minus PNI for the treatment of prostate cancer. However, RRL was more severe when PNI was utilized. The effect of SBRT and PNI on lymphocytes in prostate cancer patients could act as a model for other cancers, specifically those involving treatment with immunomodulatory agents. Future studies should focus on the clinical implications of RRL and the effects of specifically irradiating lymphoid tissues on lymphocyte biology.